Women and their symbols in Latifa Al-Dulaimi's novel 'Project Umma': A psychological study in discourse analysis - Ayad Kumar Karam, Assistant Professor Dr. (lark, 2026)
The psychological approach to the research highlights the path of pain as a path of transformation, not as a closed ending, where pain takes on a compensatory function that enhances the values ​​of dedication, tolerance, and perseverance, thus being consistent with the perspective of positive psychology, which reinterprets negative experiences.  As a potential for personal growth, the research focuses on emotional awareness as a cognitive tool that enables people to understand their feelings and be aware of the long-term consequences of their decisions, revealing the depth of the human capacity to adapt to existential complexity and exceptional circumstances.  Within this context, the feminine symbol is given a central position in feminist narratives, as it appears as a symbolic equivalent of wisdom, intuition, and emotional strength.  This symbol is not limited to the function of adornment or decoration, but rather carries complex connotations that are built on accumulated experiences that establish personalities that possess a high emotional sense that allows them to anticipate what has not yet been said or what has not yet happened, which is what strengthens the woman’s connection to her internal and external worlds in a way that is  Vital and profound.At the level of narrative language, silence is presented as a meaningful act, not devoid of significance, intersecting with speech in terms of its psychological and symbolic function.  Silence is not viewed as a lack of expression, but rather as a reflective act that reshapes the self and provides it with indirect means of defense, while speech carries a revealing energy that contributes to moments of psychological transformation and disclosure, identifying with the decisive moments in the development of narrative characters
Keywords: : love, consciousness, pain, transformation, feminist narrative, self